The Evolution of Technical Analysis : Financial Prediction from Babylonian Tablets to Bloomberg Terminals. - Lo, Andrew W. (John Wiley & Sons, Inc., 2011)
A comprehensive history of the evolution of technical analysis from ancient times to the Internet ageWhether driven by mass psychology, fear or greed of investors, the forces of supply and demand, or a combination, technical analysis has flourished for thousands of years on the outskirts of the financial establishment. In The Evolution of Technical Analysis: Financial Prediction from Babylonian Tablets to Bloomberg Terminals, MIT's Andrew W. Lo details how the charting of past stock prices for the purpose of identifying trends, patterns, strength, and cycles within market data has allowed trad.